Infrastructure And Development - Erwin Sampelalong; Ni Made Sukartini (Gorontalo Development Review, 2020)
The existence of infrastructure disparity between regions is considered as one of the factors that drive economic inequality between regions. This happened in areas that had been divided into several districts. Regional expansion is the formation of new administrative regions at the provincial level as well as cities and regencies from their parents. The most prominent reason in the discourse of regional expansion is that some regions are considered to have too large an area so that efforts are needed to facilitate administrative services and bureaucratic pruning by division /pemekaran (Koswara, 2001). Efforts to accelerate regional development can be implemented by increasing economic growth. One of them is to encourage infrastructure development in areas (districts) that are far from the provincial capital, due to the topography of the region, there are hills, valleys, swamps, and forests, thus encouraging an increase in the potential of an area / region on an ongoing basis. Infrastructure is a driver of economic progress. From the allocation of public and private financing, infrastructure is seen as a locomotive of national and regional development. Infrastructure also has an important influence on improving the quality of life and human well-being. This study aims to see whether the infrastructure of sanitation, water, electricity has a significant influence and contribution to economic growth in the regencies / cities of Papua province. This research method uses panel data regression with Random Effect Model (REM).